Killer-cell Immunoglobulin-like Receptor (KIR) gene profiles modify HIV disease course, not HIV acquisition in South African women. Issue 1 (December 2015) - Naranbhai, V.; de Assis Rosa, D.; Werner, L.; Moodley, R.; Hong, H.; Kharsany, A.; Mlisana, K.; Sibeko, S.; Garrett, N.; Chopera, D.; Carr, W.; Abdool Karim, Q.; et al.
Abstract Background Killer-cell Immunoglobulin-like Receptors(KIR) interact with Human Leukocyte Antigen(HLA) to modify natural killer- and T-cell function. KIR are implicated in HIV acquisition by small studies that have not been widely replicated. A role for KIR in HIV disease progression is more widely replicated and supported by functional studies. Methods To assess the role of KIR and KIR ligands in HIV acquisition and disease course, we studied at-risk women in South Africa between 2004–2010. Logistic regression was used for nested case–control analysis of 154 women who acquired vs. 155 who did not acquire HIV, despite high exposure. Linear mixed-effects models were used for cohort analysis of 139 women followed prospectively for a median of 54 months (IQR 31–69) until 2014. Results Neither KIR repertoires nor HLA alleles were associated with HIV acquisition. However, KIR haplotype BB was associated with lower viral loads (−0.44log10 copies/ml;SE = 0.18;p = 0.03) and higher CD4+ T-cell counts(+80 cells/μl;SE = 42;p = 0.04). This was largely explained by the protective effect ofKIR2DL2/KIR2DS2 on the B haplotype and reciprocal detrimental effect ofKIR2DL3 on the A haplotype. Conclusions Although neither KIR nor HLA appear to have a role in HIV acquisition, our data are consistent with involvement of KIR2DL2 in HIV control. Additional studies to replicate these findings are indicated.